Road Attributes and Traffic Characteristics Effects on Motorcycle Safety - I Made Sukmayasa; Dimas Adi Perwira; Arumdyah Widiati; Azwan Ezzany Azmi; Mukhammad Rizka Fahmi Amrozi (Journal of Railway Transportation and Technology, 2025)
In Indonesia, motorcycles dominate the transport landscape, with over 125 million registered motorcycles as of 2025. The country faces a significant road safety challenge, recording over 31,000 road traffic deaths annually, with motorcycles involved in many fatal crashes. Infrastructure-based interventions have shown promise in mitigating these risks. However, the implementation remains uneven, and effectiveness varies by region. Therefore, a systematic assessment of the influence of road conditions on motorcycle safety and evaluating the impact of infrastructure-based countermeasures in reducing crash risk and injury severity is needed. This study aims to systematically assess the road safety risk for motorcyclists in campus areas, with a specific focus on the role of local road attributes and traffic characteristics to propose suitable infrastructure-based countermeasures in reducing crash risk and injury severity. The method used is a road assessment tool developed by the International Road Assessment Programme (iRAP). The results show that The road attributes that play the most crucial role in determining the SRS value for a motorcycle on a road segment in the UGM campus area are those that contribute to accident likelihood: curvature, median transversability, and operating speed. Although previous research has shown operating speed to be a mediating variable rather than a direct factor in accident occurrence, it is essential to consider the factors that contribute to accidents. For intersections, the road attributes that significantly determine the level of safety are those that influence the likelihood and severity. The road attributes that influence likelihood are curvature, intersection quality, channelization, and property access points. The road attributes that influence severity are roadside severity – distance, paved shoulder width, and property access points.